Design of the Automatic Gain Control Device in the Laser Seeker - Lang, Bo; Huang, Qiang; Mi, Changwei; Liang, Yuan; Bing, Liang; Zhang, Xiaoliang; Xue, Lu; Wang, Ao (Journal of physics. Conference series, 2023)
The change of the laser echo energy received by the laser seeker during detection is too large, it is easy to saturate the input voltage of the signal processing circuit, which resulted the laser guided bombs lost the target. In this paper, an automatic gain control device for the laser seeker based on FPGA control is designed. This device is suitable for low-cost laser guided bomb because of simpleness and applicability.